Estimation of dimensions of interaction space necessary for particle acceleration in stochastic field - Ostroushko, V. (Вопросы атомной науки и техники, 2014)
It is considered electron acceleration in the field having time dependence, which differs from sinusoidal one with phase jumps introduction. The connection is found between electron energy and characteristic dimension of device, in which such energy may be achieved with considered acceleration method or with collision heating. It is shown that the acceleration in the field with jumps of phase requires much greater dimension of space for electron motion than the heating to the same energy in sinusoidal field in presence of elastic collisions. Рассмотрено ускорение электрона в поле с зависимостью от времени, отличающейся от синусоидальной введением скачков фазы. Установлена связь между энергией электронов и характерным размером устройства, в котором такая энергия может быть достигнута, при рассмотренном способе ускорения и при столкновительном нагреве. Показано, что ускорение в поле со скачками фазы требует значительно большего размера области движения электронов, чем нагрев до такой же энергии в синусоидальном поле при наличии упругих столкновений. Розглянуто прискорення електрона у полi iз залежнiстю вiд часу, яка вiдрiзняється вiд синусоїдальної введенням стрибкiв фази. Встановлено зв'язок мiж енергiєю електронiв та характерним розмiром пристрою, у якому така енергiя може бути досягнута, при розглянутому способi прискорення та при зiткненному нагрiваннi. Показано, що прискорення у полi зi стрибками фази потребує значно бiльшого розмiру областi руху електронiв, нiж нагрiвання до такої саме енергiї у синусоїдальному полi за наявностi пружних зiткнень.